Dynamic Effects of Material Damping in Active Laminates Reinforced with Piezoceramic Fibers - Pietrzakowski, Marek (Engineering Transactions, 2006)
In the paper rectangular, simply supported, laminated plates composed of classical fiber-reinforced layers and active layers of piezoelectric properties are under consideration. The aim of the study is to determine the influence of anisotropic passive damping on the active vibration reduction achieved and the sensitivity of the system to material axes' orientation of piezocomposite actuator layers. The effects of piezoceramic fiber direction and passive damping intensity are illustrated by means of the amplitude-frequency characteristics.